(untitled) (Research, Society and Development, 2021)
Introduction: Childhood leukemia is considered the most common cancer in children from 0 to 14 years old and it is related to genetics factors and, more strongly, to environmental factors, among which low-frequency non-ionizing radiation has been studied as a risk factor. Objective: To analyze scientific evidence on the association between low-frequency non-ionizing radiation sources and the occurrence of childhood leukemia. Methodology: Integrative review, whose terms were the descriptors Electromagnetic Fields and Leukemia, from Medical Subject Headings, for search in PubMed, Elsevier’s Scopus and Web of Science, and Magnetic Fields and Leukemia, from Descriptors in Health Sciences, for search in the Virtual Health Library. Two researchers selected full articles from case-control studies published from 2010 to 2020. The Rayyan QCRI software was used to analyze the articles. Results: Five articles that met the proposed methodological design were analyzed. The articles were published in English, from 2012 to 2020, and study participants were under 16 years of age. The designs of the methods for assessing exposure were heterogeneous, as was the environment analyzed. The limitations of the studies were due to the lack of evaluation of other potential external sources for the development of childhood leukemia. Conclusion: It is noteworthy that exposure to electromagnetic fields occurs from different sources and the physiological effects still need to be better explored. Robust studies are needed to analyze low frequency electromagnetic fields as a possible carcinogen to humans. Due to methodological heterogeneity and confounding variables in the analyzed articles, the authors concluded that it was not possible to demonstrate the relationship between low-frequency non-ionizing radiation sources and the development of childhood leukemia.